“Meu trabalho, meu troféu”: interações e representações em equipe na (re)produção de uma identidade artesã - SANTOS, Jonas da Silva (2021)
This dissertation is the result of a research that seeks to understand how a team of artisans from the city of Imperatriz - MA acts in the urban space from an artisan identity. Therefore, the study was based on the interactionist perspective of Erving Goffman (2012), and regarding the insertion in the field, the foundation occurred from the theoretical-methodological references of Eckert and Rocha (2008) and Pereira (2020). The investigation was carried out at the Centro de Artesanato and Beira Rio in the city, from 2019 to 2021. Through documentary verification, direct observations, image analysis and narratives of the actors, it was possible to describe the face-to-face interactions, representations, understanding the (re)production of the actors' identities and realizing how this identification is connected to the group. We understand that when acting, performers develop links between their self and the roles they play, which strengthens the order of interaction of the representation team within the social situation, understanding that by promoting these performances, the actors mobilize around the identity artisan who is connected to the artisanal product and the city's culture, seeking through this script, visibility, acceptance and occupation of urban spaces.